Using ensemble and learning techniques towards extending the knowledge Discovery Pipeline. - Yu, N Cheah; Karthigasoo, Sakthiaseelan; Manickam, Selvakumar (Universiti Sains Malaysia, 2002)

(untitled)
The generation of a huge amount of data by an enterprise is of great concern to decision makers. This problem is compounded by the many environmental challenges that an enterprise faces in the effort to produce better products and services. It is highly crucial to know what goes on in its business transactions both internally and externally and to examine the heart of an enterprise's transactions, that is its data, and to transform it into actionable knowledge through the process of knowledge discovery.